A non-covalent supramolecular dual-network polyelectrolyte evaporator based on direct-ink-writing for stable solar thermal evaporation. Issue 1 (29th November 2022) - Tang, Sihan; Lu, Xinyue; Geng, Peng; Chen, Daobing; Shi, Yunsong; Su, Jin; Zhou, Yan; Su, Bin; Wen, Shifeng
Abstract : Polymers possessing highly adjustable physicochemical properties have been accepted as ideal flexible materials for solar thermal evaporation, which is considered as an eco-friendly and progressive strategy for water reclamation. Abstract : Polymers possessing highly adjustable physicochemical properties have been accepted as ideal flexible materials for solar thermal evaporation, which is considered as an eco-friendly and progressive strategy for water reclamation. Conventional dual-network polymers based on the construction of covalent and non-covalent interactions usually involve toxic reactive monomers, initiators and organic solvents in 3D printing. The integration of additive manufacturing into the construction of supramolecular non-covalent dual-networks to achieve structural and performance optimisation remains a noteworthy part. Here we developed a 3D-printed anti-swelling polyelectrolyte evaporator consisting of k-carrageenan (CG), poly(diallyldimethylammoniumchloride) (PDADMAC), and carbon nanotubes (CNTs). CG-PDADMAC-CNT (CGP-CNT) was constructed by non-covalent supramolecular interactions (hydrogen bonds and electrostatic complexation). The exhibited "sol–gel" transition based on thermo reversible hydrogen bonds and helical structure reconfiguration facilitated three-dimensional shaping, while strong electrostatic complexation stabilized the evaporator structure. As a proof-of-concept, the 3D-printed evaporator was intrinsically antibacterial and exhibited remarkable swelling resistance (water bath at 100 °C for 14 days, pH = 13) to a harsh water environment and stable solar thermal evaporation (2.3 kg m −2 h) under 1 sun irradiation, which was one of the prominent values among the evaporators prepared by direct-ink-writing (DIW).